1923
DOI: 10.1098/rspb.1923.0024
|View full text |Cite
|
Sign up to set email alerts
|

The determiners of cellulose structure as seen in the cell-wall of cotton hairs

Abstract: and Doublers Association, Bollington.) .[P lates 5 and 6.]This analysis of cell-wall structure as seen in cotton hairs began with the inference that diurnal growth rings existed therein. After this inference had been confirmed* it was shown that spiral structures common to all the growth rings were present,j* and that these were of at least two kinds, quick or " pit spirals^ and slow spirals corresponding to objects figured by De Mosenthal. § In our last communication we concluded that these two kinds of spira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1937
1937
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Our AFM investigation of cotton ®bers builds upon earlier analyses that primarily dealt with qualitative aspects of ®ber surface morphology (Balls 1923;Farr 1934;Anderson and Kerr 1938;Tripp et al 1954;Rollins et al 1965;Westafer and Brown 1976;Ryser 1985). The ®ber surface is characterized by an extensive series of low furrows and ridges that are formed by bundles of underlying secondary wall micro®brils arranged in a spiral pattern around the longitudinal axis of the ®ber (Tripp and Rollins 1952).…”
Section: Introductionmentioning
confidence: 99%
“…Our AFM investigation of cotton ®bers builds upon earlier analyses that primarily dealt with qualitative aspects of ®ber surface morphology (Balls 1923;Farr 1934;Anderson and Kerr 1938;Tripp et al 1954;Rollins et al 1965;Westafer and Brown 1976;Ryser 1985). The ®ber surface is characterized by an extensive series of low furrows and ridges that are formed by bundles of underlying secondary wall micro®brils arranged in a spiral pattern around the longitudinal axis of the ®ber (Tripp and Rollins 1952).…”
Section: Introductionmentioning
confidence: 99%
“…Perimeter, cell-wall area, and circularity increase with an increase in coarseness when the maturity of the fibers is maintained constant, while cell-wall thickness remains practically constant. 4. Perimeter decreases, circularity, and cell-wall thickness increase, while wall area remains practically constant with increase in maturity when the fineness of the fibers is maintained constant.…”
Section: Conclusion -mentioning
confidence: 94%
“…Detailed work by Balls [3,4] describes the structure of the cellulose wall of cotton hair in relation to its development and the origin of spiral structure.…”
Section: Introductionmentioning
confidence: 99%
“…The crosslinking seemed to cease at 190°C. Beyond this temperature, the changes in 2 and I 2 suggested that crosslinking changed the fiber structure from spiral 29 to a three-dimensional network. 24 After 210°C, the thermal degradation of the cotton fibers took place.…”
mentioning
confidence: 95%